(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
A model for diffusion in grains, through the drying process in the form of moisture removal, discussed through this work. While in drying, the moisture leaves the product as vapour or gas. This is achieved by impairing energy to the moisture molecule or changing the environment, so that the molecule will have sufficient latent energy to leave the product. Hence it is the process, which is intended to remove moisture from a feed substance so that the feed becomes dry as final product. Moisture reduction can also be achieved by mechanical methods. Using the pressure gradient as the deriving force with combined flux, we get a system of partial differential equation which will be then solved with the help of MATLAB 7.0 and finally the graphs shows the variation of moisture with respect to diffusion coefficient at different temperature and as well as variation of moisture with the time.